New species of Metynnis Cope, 1878 (Characiformes: Characidae) from the rio Paraguay basin, Mato Grosso State, Brazil - Pavanelli,Carla S. (2009)
A new species of Metynnis is described from the rio Cuiabá and rio Manso drainages, in the upper rio Paraguay basin, Mato Grosso State, Brazil. This laterally compressed species, which rarely exceeds 140 mm in SL, is readily distinguished from other members of the genus Metynnis by having 100-110 lateral-line scales, 48-56 rows of scales above the lateral line, 32-36 circumpeduncular scales, 22-24 gill rakers, 38 vertebrae, singular color pattern, and relatively smaller snout, width, and head length.